2015
DOI: 10.1007/s10661-015-4603-6
|View full text |Cite
|
Sign up to set email alerts
|

Space–time LAI variability in Northern Puglia (Italy) from SPOT VGT data

Abstract: The vegetation space–time variability during 1999–2010 in the North of the Apulian region (Southern Italy) was analysed using SPOT VEGETATION (VGT) sensor data. Three bands of VEGETATION (RED, NIR and SWIR) were used to implement the vegetation index named reduced simple ratio (RSR) to derive leaf area index (LAI). The monthly average LAI is an indicator of biomass and canopy cover, while the difference between the annual maximum and minimum LAI is an indicator of annual leaf turnover. The space–time distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…On the other hand, the LAI annual mean shows a dropdown in 2005 but not a marked general trend ( Figure 6A), denoting that at the annual scale, the heterogeneity in vegetation cover and local effects prevails in interannual climatic forcing. Consistently, it has been already observed in this region, that the LAI Spatial Mean behavior in time is affected more by mean temperature and rainfall monthly distribution than by annual rainfall amount [31]. In addition, ( Figure 6C) shows a combined plot of LAI Spatial Mean and LAI Spatial STD.…”
Section: Vegetation Cover Changes Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, the LAI annual mean shows a dropdown in 2005 but not a marked general trend ( Figure 6A), denoting that at the annual scale, the heterogeneity in vegetation cover and local effects prevails in interannual climatic forcing. Consistently, it has been already observed in this region, that the LAI Spatial Mean behavior in time is affected more by mean temperature and rainfall monthly distribution than by annual rainfall amount [31]. In addition, ( Figure 6C) shows a combined plot of LAI Spatial Mean and LAI Spatial STD.…”
Section: Vegetation Cover Changes Analysissupporting
confidence: 88%
“…Mainly because of the relatively short period of the study (15 years), the results showed a prevalent impact of the human driving factors in comparison with the physical ones related previously in the literature, such as [31,33,44,69] in affecting the year-to-year changes in the vegetation cover.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Vegetation indices were used to enhance the detection of vegetated areas: leaf area index (LAI) and modified soil adjusted vegetation index (MSAVI). LAI is commonly used in agronomic and environmental modeling [36][37][38][39][40][41]. In this study, LAI was evaluated through a semi-empirical model derived from the Lambert-Beer law (1): LANDSAT-TM digital numbers were firstly converted to Top of Atmosphere (TOA) reflectance and corrected for sun elevation angle by using gains, offsets, and brightness temperature coefficients provided in each scene metadata and related standard procedures suggested by the USGS [34].…”
Section: Landsat Data Processingmentioning
confidence: 99%
“…LAI is commonly used in agronomic and environmental modeling [36][37][38][39][40][41]. In this study, LAI was evaluated through a semi-empirical model derived from the Lambert-Beer law (1):…”
Section: Landsat Data Processingmentioning
confidence: 99%